PERAN INTERAKSI SOSIAL TERHADAP KEPUASAN HIDUP LANJUT USIA - Fitriyadewi, Luh Putu Wiwin; Suarya, Luh Made Karisma Sukmayanti (Program Studi Sarjana Psikologi, Fakultas Kedokteran, Universitas Udayana, 2016)
A person’s mental, social functioning and psychological also health will decreased during the late adulthood phase. Those are the obstacles for the people who want to feel the enjoyment of life. People will assume that they have high life satisfaction when they still did the daily activity that they used to do. One of the thing that can make people satisfy with their life is social interaction. Social interaction happened in many aspect of our life not only just in family but also in bigger social life such as neighborhoods, friends, friends at work, etc. The form of social interaction are say hello, smile, and also when a person take a part in problem solving process . This research is a quantitative research using simple regression analysis and using purposive sample technique as the technique sample. Subject in this research are a person age 60 till 80 years old. The instrument in this research is social interaction scale with 15 items and the coefficient reliability = 0,788. The result of this research is show R= 0,001 (p<0,05) thus can be stated that there is a relationship between social interaction with life satisfaction of a late adulthood, which means that the higher social interaction of a person will make a high life satisfaction to their life but if a person have low social interaction, the life satisfaction will be low too. R square = 0,101 which means that the social interaction have contributed 10,1% toward life satisfaction. 100 subject in this research are the people who have a good social interaction and life satisfaction.Keyword: social interaction, life satisfaction,late adulthood.